IDENTIFICATION OF BEGINNING READING DIFFICULTIES IN CLASS II PRIMARY SCHOOL STUDENTS - Herlina, Herlina; Mayui, Novin; Fasli, Muhammad; Aras, Nurul Fitria (Indonesian Journal of Educational Development (IJED), 2024)
This research aims to determine: 1) the difficulties faced by students in beginning reading, 2) teachers' efforts to overcome students' beginning reading difficulties, and 3) factors that cause difficulties in beginning reading. This research uses a qualitative approach with a phenomenological design. The research subjects were 14 students in class II of SD Inpres Bumi Sagu. Data was collected using observation, interviews and document study techniques. The data analysis used is data condensation, data presentation and drawing conclusions/verification. The results of this research show that the difficulties experienced by students in beginning reading are that they do not know letters, are slow in reading, students cannot yet read, letters and words are often confused, and have difficulty spelling. The factors that cause students to experience difficulty in reading at the beginning are internal factors which include the child's psychology and external factors, namely the family environment and the learning environment at school. The teacher's efforts to overcome this problem are by applying the EGRA teaching method, spelling method, sound method (phonic), syllabic method (silabel) and the method of the word institution.